Resposta :
OLÁ
[tex]4x - 1 = 3 \times (x - 1) \\ 4x - 1 = 3x - 3 \\ 4x - 3x - 1 = - 3 \\ 4x - 3x = - 3 + 1 \\ x = - 3 + 1 \\ x = - 2 \\ espero \: ter \: ajudado[/tex]
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/d16/23d18f70e7ca96c5b40be6325dbf4ff3.jpg)
Explicação passo-a-passo:
4x-1=3(x-1)
4x - 1 = 3x -3
4x -3x = -3 +1
X = -2
OLÁ
[tex]4x - 1 = 3 \times (x - 1) \\ 4x - 1 = 3x - 3 \\ 4x - 3x - 1 = - 3 \\ 4x - 3x = - 3 + 1 \\ x = - 3 + 1 \\ x = - 2 \\ espero \: ter \: ajudado[/tex]
Explicação passo-a-passo:
4x-1=3(x-1)
4x - 1 = 3x -3
4x -3x = -3 +1
X = -2